TRADISI HOSPITALITAS UNTUK PENDIDIKAN PERDAMAIAN DI POSO - Ones Morokuhi (UKI Press, 2017)
The research in this paper leads to peace education in Poso. Local wisdom approach focus to achieve it. Local wisdom in question is a tradition of cultural in sintuwu maroso and padungku. Researchers considered that culture sintuwu maroso and padungku a primal's hospitality owned Poso then and now. The distinctive feature of this research center at the local wisdom area. That approach is not without reason. Social unrest conflicts that have occurred in Poso, leaving wounds that are difficult unresolved grudges. Seventeen years ago the conflict was going on, now remaining trauma and feels haunted. Yet the return of all refugees to their original place, not awakening back all the buildings or houses in the former debris destruction mass, separation is expressly settlements Islamic-Christian, social community is still limited, and military approach that is very dominant, not apart from monitoring the author. Watched it is balanced with the security situation, a conducive atmosphere andhospitality of the people of Poso today. Objectives achieved in this study were (1) to find out how the understanding and meaning of the Poso community’s hospitality (2) to find out ways of appreciation and practice of cultural sintuwu maroso and padungku as a form of tradition's hospitality in Poso and (3) to determine the role and the application of hospitality in traditions of cultural sintuwu maroso and padungku for peace education in addressing the conflict in Poso. The data collection process is conducted qualitatively. Interviews and observations is his method, followed by a description of the data. Analysis of data using analytical approachto Theology-CRE (Christian Religious Education). This approach was chosen because they are the research student of CRE. After conducting research and data analysis as a whole, the picture of hospitality in Poso this time will be presented in a straightforward and unequivocal. Likewise, appreciation and practice of cultural sintuwu maroso and padungku in everyday life. In the end, the author proposes an approach to education for peace in Poso, that is approach through cultural traditions in sintuwu maroso's hospitality and padungku Key words: Hospitality, Sintuwu Maroso, Padungku, Peace Education.